Benchmarking philanthropy in Europe - Salgueiro, Tomé Guerreiro de Oliveira (2019)
The lack of organized information about activities and the performance of players in the third sector hinders the development of more and better philanthropy. Furthermore, the great diversity of countries, languages and more importantly giving cultures within Europe, is not inviting of international cooperation, creating challenges when learning from other practices across the continent. This thesis, and the major project it encompasses, is the first step by the Calouste Gulbenkian Foundation to benchmark and learn from the best initiatives in some of the most developed and fastest growing giving cultures in Europe.